Sedation Strategies for Procedures Outside the Operating Room - Jo, Youn Yi; Kwak, Hyun Jeong (Yonsei medical journal, 2019)
With the rapid development of diagnostic and therapeutic procedures performed outside the operating room (OR), the need for appropriate sedation care has emerged in importance to ensure the safety and comfort of patients and clinicians. The preparation and administration of sedatives and sedation care outside the OR require careful attention, proper monitoring systems, and clinically useful sedation guidelines. This literature review addresses proper monitoring and selection of sedatives for diagnostic and interventional procedures outside the OR. As the depth of sedation increases, respiratory depression and cardiovascular suppression become serious, necessitating careful surveillance using appropriate monitoring equipment.